Aspek Hukum atas Rencana Perdamaian Yang Diajukan Kedua Kalinya dalam Mekanisme PKPU Selama Tahapan Kepailitan - Hessy Oktiarifadah; Elisatris Gultom; Anita Afriana (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines legal deviations in the implementation of the Suspension of Debt Payment Obligations (PKPU) mechanism, specifically regarding the approval of a peace settlement submitted for the second time after the debtor is declared bankrupt. The study highlights the Supreme Court Decision No. 648K/Pdt.Sus-Pailit/2021, which ratified the second peace settlement in the case of PT Prospek Duta Sukses. This decision is deemed contradictory to the principle of a single peace settlement, as stipulated in Articles 289 and 292 of Law No. 37 of 2004 on Bankruptcy and PKPU, and further reinforced by Supreme Court Circular Letter (SEMA) No. 5 of 2021, which states that a peace settlement in bankruptcy can only be conducted once. Using a normative juridical method, this research analyzes the legal reasoning used by the panel of judges in approving the second peace settlement and evaluates its impact on legal certainty and protection for creditors, who are the affected parties in the bankruptcy process. The approval of a second peace settlement after the debtor is declared bankrupt creates legal uncertainty, as the existing provisions do not provide for more than one peace settlement. Additionally, this decision potentially harms creditors by prolonging the settlement of debts, which should have been clear, thus allowing room for misuse of legal procedures. The findings of the study show that the approval of this second peace settlement not only contradicts the fundamental principles of law but also risks harming creditors, who should be protected by the bankruptcy system to ensure their rights are fairly met. Therefore, this research suggests that consistent application of the law, in line with existing provisions, is necessary to uphold the principles of justice, legal certainty, and the credibility of the national bankruptcy system. Furthermore, reforms in regulations or law enforcement are needed to ensure that legal practices operate in accordance with principles that are fair and transparent.